Integration of sustainable development in the strategy implementation process: proposal of a model - Simas, M. J.; Lengler, J.; António, N. (Corporate Governance, 2013)
Purpose ? This paper seeks to integrate sustainable development, based on the application of the extended bottom line (EBL-GMS®) concept, into the implementation of organizational strategy with the relevant stakeholders. As a result, a theoretical model is proposed. Design/methodology/approach ? The paper reviews selected literature to propose and analyse how sustainable development can be integrated into the implementation of organizational strategy. Findings ? This paper proposes a conceptual model that deals with the relationship between sustainable development and implementation of organizational strategy with the distinct stakeholders of a company. In the proposed model, authors indicate how the concept of sustainable development could be operationalized through each of the organizational stakeholders. Originality/value ? Companies, as dynamic systems, are relevant in the implementation process of sustainable development, which requires this concept to be fairly applicable. In general, only one of the bottoms of the triple bottom line (TBL) has been considered, being essential to integrate and consolidate, through an ethical and balanced manner, the economic, social, environmental and corporate identity elements. This paper addresses a critical condition for companies operating in highly competitive contexts: sustainable development and its relationships with strategy implementation. The originality lies in the fact that no studies have analysed the relationship between the sustainable development concept and organizational strategy implementation, based on the operationalisation of the extended bottom line (EBL-GMS®) concept.